Agricultural biotechnology in India: ethics, business and politics. (11th March 2005) - Gupta, Anil K; Chandak, Vikas
This paper deals with the case of Bt cotton in Gujarat, India, as an illustration of how public policy chickens out when large-scale violation of ethical and scientific norms takes place with positive business outcomes. Entrepreneurial spirit has created a unique case of farmer participatory research whereon farm crosses are being made between Bt cotton varieties and other released varieties. New production cycles are being created by farmers who have extended the life of the crop from six months to nine months to reap advantage of continuous flowering and thus higher yield. All this has happened in an unauthorised manner, with full public knowledge and despite complaints of Monsanto and MAYHCO about Navbharat Seed Company having "stolen" their Bt gene. Farmers are happy, politicians do not care and regulatory agencies are satisfied that sending a few committees to enquire is all that they needed to have done. This article presents a review of important studies in the context of the Bt adventure in Gujarat and discusses the findings obtained in a farmer survey on experience and perception of Bt cotton in Gujarat.